Pedagogical Technologies and Cognitive Development in Secondary Education - Akhmetova Assel; Karmanova Zhanat; Demissenova Shnar; Sadvakassova Nurgul; Koshkumbaev Kanat (De Gruyter, 2024)
The model for implementing pedagogical technologies to the develop cognitive processes of secondary education students is highly significant in the present era.